2019
DOI: 10.3390/biom9040140
|View full text |Cite
|
Sign up to set email alerts
|

Organellar DNA Polymerases in Complex Plastid-Bearing Algae

Abstract: DNA replication in plastids and mitochondria is generally regulated by nucleus-encoded proteins. In plants and red algae, a nucleus-encoded enzyme called POP (plant and protist organellar DNA polymerase) is involved in DNA replication in both organelles by virtue of its dual localization. POPs are family A DNA polymerases, which include bacterial DNA polymerase I (PolI). POP homologs have been found in a wide range of eukaryotes, including plants, algae, and non-photosynthetic protists. However, the phylogeny … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(38 citation statements)
references
References 49 publications
7
31
0
Order By: Relevance
“…Pioneering studies demonstrated that the previously described mitochondrion-localized DNA polymerases, namely Polγ, POP, trypanosomatid PolIA-D belong to family A [10,23]. Thus, we surveyed family A DNA polymerases in both public and in-house transcriptome data of four kinetoplastids, four diplonemids, and six euglenids (14 species in total).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pioneering studies demonstrated that the previously described mitochondrion-localized DNA polymerases, namely Polγ, POP, trypanosomatid PolIA-D belong to family A [10,23]. Thus, we surveyed family A DNA polymerases in both public and in-house transcriptome data of four kinetoplastids, four diplonemids, and six euglenids (14 species in total).…”
Section: Resultsmentioning
confidence: 99%
“…Trypanosomatid PolIB, C and D were shown to be closely related to each other but remote from PolIA in previous phylogenetic studies [10,23]. In this section, we describe the distribution and evolution of PolIB, C, D and "PolIBCD-related" DNA polymerases in Euglenozoa.…”
Section: Polib C D and "Polibcd-related" Dna Polymerases In Diplonmentioning
confidence: 90%
See 1 more Smart Citation
“…DNA and RNA metabolism (C) DNA replication and repair Unlike animals and fungi, which utilize a T3/T7 bacteriophage-like DNA polymerase (DNAP) γ for mtDNA replication [33,78], eukaryotes other than opisthokonts use a bacterial Pol A-like (Pol I) DNAP. This enzyme was given the name "plant organellar DNA polymerase" (POP) by Moriyama et al [79,80] but has since been identified also in protists [33,81]. It constitutes a distinct phylogenetic group without close relatives and hence of unclear origin [33,[79][80][81].…”
Section: Other Respiratory Proteinsmentioning
confidence: 99%
“…This enzyme was given the name "plant organellar DNA polymerase" (POP) by Moriyama et al [79,80] but has since been identified also in protists [33,81]. It constitutes a distinct phylogenetic group without close relatives and hence of unclear origin [33,[79][80][81]. In bacteria, Pol I plays an essential role in replication through its 5′-to-3′ exonuclease activity, which together with the 5′-to-3′ polymerase activity catalyzes the removal of RNA primers from replication intermediates.…”
Section: Other Respiratory Proteinsmentioning
confidence: 99%